Screenwriting the body in Fireflies: An analysis of the devising and writing process - Dooley, Kath (2016)
This article explores the development of corporeal themes in a screenplay by analysing the initial developmental stages of a feature film tentatively titled Fireflies as case study. In early 2015 I decided that I wanted to write a screenplay about two teenage girls’ experiences of negotiating social media and dating apps such as Tinder. In doing so I hoped to explore notions of intimacy and bodily control. My practicebased screenwriting research in this area is concerned with the way that recording observations of the female form on video and in still images can inform the representation of female agency and sexuality in a screenplay. In particular, I draw upon the approach of Virginia Pitts, who used video recordings from actor workshops to assist in the development of a short film script. This approach is underpinned by the theoretical concept of ‘kinaesthetic empathy’ as a means to form connections between writer, actors and audience. Using a reflexive methodology to mediate the screenplay development process, I respond to scripting workshops that involved two female actors, undertaken to interrogate the themes of the screenplay. These workshops involved the use of mobile phones and video cameras to record footage of bodies, which was reviewed to inform the writing of the first draft script. I examine a range of literature that presents case studies of innovate ways to ‘screen write the body’, before applying various approaches in the early development of Fireflies. Key points include a consideration of character presence and movement rather than psychology as a focus of the film narrative; and the use of screens (mobile phone and video) to write for the screen.